A retrospective study on various methods used in second trimester MTP at KIMS hospital and research centre, Bangalore - J., Sankalpa A.; T., Jayanthy; A., Sanvithi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Despite the fact that majority of abortions are performed in the first trimester, 10-15% of abortions have taken place in the second trimester period globally because of delayed diagnosis of fetal anomalies and failure to recognize an undesired pregnancy in the first trimester. This study aims to describe the various methods used in inducing second trimester abortions and to analyse the efficacy and safety profile of these methods. Methods: Retrospective observational study. This study analysed case records of 30 patients who underwent second trimester abortion between the gestations of 12 and 28 weeks. All case records of patients who underwent second trimester abortion between the gestation 12 and 28 weeks from 1st January 2021 to 1st August 2021 at the department of obstetrics and Gynaecology, KIMS hospital and Research Centre, Bangalore was analysed. Dilapan-s (hygroscopic mechanical dilator), Foley’s and mifepristone for cervical ripening followed by varying doses of misoprostol are the different methods studied in this study population. Results: Most of the patients in study population belonged to the age group of 28-32 years. 60% patients underwent MTP between the gestational ages of 16-20weeks.The commonest indication for MTP was fetal anomaly. Conclusions: Mifepristone group had short induction to abortion interval but was associated with higher rates of retained placenta bits. Foleys group had the longest induction to abortion interval but reported no complications.